الزيوليت الانواع والاستعمالات - شيماء, تجاني; عائشة, حريز بكار; آمنه, عوينات (Université d'El Oued, 2022)
"Zeolite is a solid porous aluminum silicate material, of two types, natural and synthetic. One of the most important methods of preparing zeolite industrially is the crystallization method. Zeolite has many uses in a variety of fields, including: as catalysts in industry, agriculture, medical applications, biomass conversion, construction, in addition to absorbing heavy and toxic metals from water and soil and removing air pollution. for its physical and chemical properties. The discovery of new ways to manufacture zeolite in the future and search for other areas of uses. ""الزيوليت عبارة عن مواد صلبة مسامية من سليكات الألمنيوم، له نوعين طبيعي و اصطناعي. من أهم طرق تحضير الزيوليت صناعيا هي طريقة التبلور. للزيوليت استعمالات عديدة في مجالات متنوعة منها: كمحفزات في الصناعة، الزراعة، التطبيقات الطبية، تحويل الكتلة الحيوية، البناء، إضافة الى امتصاص المعادن الثقيلة والسامة من المياه و التربة و إزالة تلوث الهواء، وهذا راجع لخصائصه الفيزيائية و الكيميائية. كما يمكن تحسين و اكتشاف طرق جديدة لتصنيع الزيوليت في المستقبل و البحث عن مجالات أخرى للاستعمالات. "
مذكرة ماستر تخصص هندسة طرائق
Keywords: zeolite, zeolite natural, synthetic zeolite, porous materials, catalysts, Adsorption; الزيوليت، الزيوليت الطبيعي، الزيوليت الصناعي، المواد المسامية، المحفزات، الامتصاص.